(untitled) (International journal of artificial intelligence, 2025)
A profound understanding of a text requires an analysis of native speakers’ cognitive and social knowledge not only within a single cultural framework but also in the broader context of intercultural communication. This article presents a linguocultural analysis of place names found in the works of Abdulla Qahhor. It offers insights and reflections on the linguistic and cultural features of the names “Shohimardon,” “Taxti Sulaymon,” and “Teshiktosh”